Theoretical and Spectroscopic Investigations on Ionogels - Hussan, Safna (Cambridge Scholars Publisher, 2019)
Today, an enormous amount of research is devoted to immobilizing ionic liquid (IL) for electrochemical applications, due to its potential as an excellent substitute for liquid electrolytes. Among the more well-known strategies, entrapping IL in the polymer matrix can be considered as a feasible, low cost method for large scale production of ionogel. The versatility of both IL and polymer chemistry allows us to develop an infinite number of ionogels. This book provides a complete overview of this subject, moving from the development of ionogel to its application. It covers characterization tech.